THE POLITICS OF QIR?’?T: STATE POWER AND THE CANONIZATION OF QUR’ANIC RECITATION IN EARLY ISLAM - Siti Khodijah; Iffah Muzammil; Moch. Rafly Try Ramadhani (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
The study of qir?’?t in Islam has traditionally centered on linguistic and phonetic dimensions. However, it also intersects significantly with the dynamics of political authority and canon formation in Islamic history. Using a historical-analytical approach, this study examines the role of political power in the codification and standardization of qir?’?t, focusing on critical episodes such as the compilation of the mu??af under Caliph ‘Uthm?n ibn ‘Aff?n, administrative interventions during the Umayyad dynasty, and the canonization of the seven qir?’?t by Ibn Muj?hid, later expanded to ten by Ibn al-Jazar?. Drawing on classical Islamic sources and contemporary academic literature, the study demonstrates that qir?’?t orthodoxy was shaped not only by scholarly consensus, but also by strategic political interventions in response to socio-political imperatives. By exploring the intersection of religion, power, and the construction of Qur’anic recitational authority, this research contributes to a deeper understanding of how the political construction of religious orthodoxy and the canonization of sacred texts in Islam.